2006
DOI: 10.1158/0008-5472.can-06-2249
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic Action of the Androgen Receptor Sensitizes Prostate Cancer Cells to Taxane-Based Cytotoxic Insult

Abstract: Prostate cancer cells are dependent on androgen for growth and survival; as such, inhibition of androgen receptor (AR) activity is the first line of intervention for disseminated disease. Recently, specific cytotoxic agents have been shown to extend survival times in patients with advanced disease. Given the established ability of androgen to modify cell survival in prostate cancer cells, it is imperative to determine the effect of the hormonal environment on cytotoxic response. Here, we show that the response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 62 publications
3
12
0
Order By: Relevance
“…One of the most difficult challenges in treating these patients, however, is the identification of patients with incompletely endocrine-responsive tumor who should receive a chemo-endocrine treatment. In prostate cancer, it has been suggested that knowledge of AR action in promoting cell proliferation can be used to design strategies that maximize cell death in response to cytotoxic therapy [27]. The results of the present study suggest that AR could be an important parameter for designing specific systemic treatments for the patients with ER-positive breast cancer.…”
Section: The 2009 St Gallen Recommendations Consider Endocrine Theramentioning
confidence: 65%
“…One of the most difficult challenges in treating these patients, however, is the identification of patients with incompletely endocrine-responsive tumor who should receive a chemo-endocrine treatment. In prostate cancer, it has been suggested that knowledge of AR action in promoting cell proliferation can be used to design strategies that maximize cell death in response to cytotoxic therapy [27]. The results of the present study suggest that AR could be an important parameter for designing specific systemic treatments for the patients with ER-positive breast cancer.…”
Section: The 2009 St Gallen Recommendations Consider Endocrine Theramentioning
confidence: 65%
“…shCon1 LNCaP cells and L4-shCon LAPC-4 cells (7.8 Â 10 5 cells per 10-cm dish) were infected with p16INK4a adenovirus for 12 h as previously described (19). Following wash PBS, cells were cultured for an additional 36 to 48 h and then fixed in 95% ethanol, stained with propidium iodide (0.2 Ag/AL), and subjected to flow cytometry as described previously (20). Histograms represent f10,000 cells.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have reported that response to taxanes, the only chemotherapeutic agent proven to be efficacious in prolonging overall survival in patients with prostate cancer, is maximized under conditions of AR activity. 88 On the other hand, HIF-1α overexpression in hypoxic cells has been shown to reduce the effectiveness of microtubule-disrupting agents in a drug-dose-dependent manner in human ovarian cell lines. 89 Similarly, we have reported sensitivity of hypoxic prostate cancer cells to docetaxel and a novel microtubule disrupting agent pyrrolo-1,5-benzoxazepine 15 (PBOX-15).…”
Section: Treatment Resistancementioning
confidence: 99%